An integrated approach to address the expansion planning problem of distribution networks under competition - Maria Teresa Ponce de Leão (2002)
In this paper we describe a model to evaluate long term marginal prices in distribution networks considering investment decisions and uncertainties related to load evolution. These prices, although harder to compute, display very interesting properties in terms of long term stability and of ensuring revenue reconciliation between costs and remunerations. The model identifies a first set of feasible solutions according to several criteria and allows the user to select the final expansion strategy according to his preferences. The first of these two phases uses Simulated Annealing given its flexibility, easiness of application, ability to deal with discrete decisions and to escape from local optima. At a final section, the approach is illustrated using a case study based on a realistic distribution Portuguese network.